UVC germicidal lamp-assisted crosslinking of globular polyacrylate stabilizer for CdS nanoparticles. - Galeon, Gilbert Joey Ajoc (2007.)
Polyacrylic acid as the template for UV-radiation assisted synthesis of nanoparticles has been used. Polyacrylic acid in solution is known to collapse into globular conformation by adding salt (e.g. CD+2). The globular conformation of the polycrylates will engulf the metal cations preventing them from aggregation. This conformation of the polyacrylic acid can be made permanent by crosslinking them using a UV-radiation. UV-radiation can form C-radicals within the polyacrylate monomer units which will intermolecularly and intramolecularly from bonds through time making ther confrontation permanent. During the crosslinking process, the cation will be reduced using a reducing agent., In this study, CdS-nanoparticles is synthesized using Cd+2 as the metal salt and thioacetamide as the reducing agent. UVC-germicidal lamp was used as the source of the UV-radiation that crosslinked the polyacrylate stabilizer. Scanning electron microscopy shows the image of the morphology and sizes of the nanoparticles produced. UV-vis spectroscopy was used to show the absorbance of the CdS-nanoparticles fluorescene spectrometry was used to show its emission spectra.
Thesis (Undergraduate, Bachelor of Science in Chemistry) College of Arts and Sciences, University of the Philippines Visayas, Miagao, Iloilo.
Keywords: Globular Polyacrylate Stabilizer